NIGERIANS UTILISATION OF CODE-MIXING AS COMMUNICATIVE DEVICES - Iyabode Omolara Akewo Daniel (English Review: Journal of English Education, 2016)
The importance of communication as a central idea in language usage cannot be over-emphasised. This seems to inform how many Nigerian speakers make extensive use of the mixture of indigenous languages and the English language in one and the same breath. It seems to reveal a kind of perception of reality in two ways at the same time. They seem to go through the process of thinking in diverse ways at the same time. This study thus seeks to find out the extent to which the average Nigerian user of the English language makesÂ  intelligible contribution to discourses. How much sense is made to and by interlocutors in the course of their discussions? To what extent is reality to them influenced by their knowledge of the English language? The extent of the indigenisation process is also of interest to the study. The expectation is that such contact should be to the advantage of one or the other of the languages in contact. Real time linguistic data were collected and analysed, using linguistic levels as base to access the extent to which Nigerian indigenous languages have been able to influence the English language. The finding shows that codemixing is an important part of the Nigerian communication process and has enabled the vernacularisation of the English language to a very large extent. This has produced a new spatial identity that reveals the Nigerianâ€™s domination of the colonial English language.Keywords: Code-mixing, Communication, Language usage, English vernacularisation, Nigerian indigenous languages, Spatial identity